Rechargeable Aqueous Microdroplet - Phan, Chi (American Chemical Society, 2014)
Directional and controllable transportation of microdroplets is critical for emerging micro- and nanotechnology, in which the conventional mechanical energy generation is not applicable. This Letter shows that an aqueous microdroplet can be charged for controlled motion in electrostatic potential, which was created by differentiating pH, between two oil/water interfaces. The directional motion of the droplet, <100 micro-meters in diameter, was obtained with a constant velocity of ~1 mm/s. The force analysis showed that the droplet surface was charged and recharged oppositely byion transfer through interfacial layers, without significant mass transfer. The charging and recharging cycles were recorded continuously with a single droplet over 100 times. The energy for motion was generated from pH neutralization, which is the simplest aqueous reaction. This is the first time that the phenomenon is reported. The phenomenon can be employed as an efficient and robust method to convert chemical to mechanical energy for miniaturized devices and microprocesses.